Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions - Kiel, Steffen; Sami, Marco; Taviani, Marco (European Journal of Taxonomy, 2023)
Here, we report on 33 molluscan species from Miocene ’Calcari a Lucina’ hydrocarbon-seep deposits in northern Italy. Three new species are described: the chilodontaid gastropod Putzeysia diversii sp. nov., the lucinid bivalve Miltha (sensu lato) romaniae sp. nov., and Sisonia ultimoi sp. nov., a heterodont bivalve of uncertain taxonomic affinity. Fourteen species are described in open nomenclature. The common but enigmatic gastropod species Phasianema taurocrassa is here suggested to belong to the seguenzioid genus Cataegis. Most gastropod species are inhabitants of the deep-sea floor in general, and are not restricted (obligate) to sites of hydrocarbon-seepage. The gastropod Putzeysia diversii sp. nov. and the bivalve Sisonia ultimoi sp. nov. are the geologically oldest members of their genera known to date. While the genus Putzeysia is geographically restricted to the NE Atlantic Ocean and the Mediterranean Sea, Sisonia ultimoi sp. nov. represents another link of the Miocene Mediterranean seep fauna to that of the central Indo-West Pacific Ocean.